Filozofia wojny Antona Kiersnowskiego - Szpoper, Dariusz (PRAWO i WIĘŹ, 2025)
This paper presents Anton Kiersnowski’s concept of war, as set out in his 1939 work Philosophy of War. In this text, war is analysed as a phenomenon with moral and spiritual dimensions. Kiersnowski emphasises the ethical and religious dimensions of armed conflict, rejecting both pacifism and the theory of total war. He criticises Clausewitz and Lenin as architects of destructive ideologies. He portrays war as an inevitable yet pathological event that must be understood within the context of a Christian conception of justice. The paper calls for the revival of a spiritual Russian military doctrine rooted in pre-revolutionary traditions. The paper examines various historical conflicts, including Polish-Russian relations, through the lens of just war theory, asserting that only wars waged in defense of spiritual values and national-religious unity can be regarded as truly legitimate.